A Comparative Study of the Efficiency of two Different Glass Ionomer Using ART Technique in a Group of Egyptian Children with Autistic Spectrum Disorder - Ghada A Elbaz; Mohamed Sherif M Salah Eldin; Walaa H M Mabrok (International Journal of Oral and Craniofacial Science - Peertechz Publications, 2015)
Aim: The aim of the study was to evaluate and compare the effect of conventional glass ionomer cement and Nano-glass ionomer using atraumatic restorative technique (ART) in a group of Egyptian autistic children. Materials and Methods: Thirty autistic patients had cavitated lower first primary molars (class I only) were included in this study. According to the type of restorative material used, the children were classified into 2 groups: (Group I) their teeth were restored with conventional glass ionomer, (Group II) their teeth were restored with Nano-glass ionomer (ketac N 100). All children were checked clinically, radio graphically and for bacterial count evaluation at baseline (before treatment) and after 1 week, 2 weeks, 1 month, 3 months and 6 months. Results: After 6 months, group I showed statistically significant higher prevalence of pain, food stagnation, restoration defects and widening of lamina dura than group II while for bacterial count evaluation, the microbiological assay results show there was no statistically significant difference between the two groups. Conclusion: The results indicate that Nano-glass ionomer can be considered a successful alternative restorative material for ART technique with promising results in treatment of children with autistic spectrum disorder.